Management of Zoning Path New Student Admission Strategy - Lariani, Eka; Widayatsih, Tri; Fitriani, Yessi (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study was to determine the management of zoning student admissions at SMAN 8 Palembang. This is a qualitative descriptive study. The subjects were the principal, the curriculum head, the head of the committee for new student admission, the students’ guardians, and the students of SMA Negeri 8 Palembang. Observations, interviews, and documentation were used to collect data. The results demonstrated that the management of zoning student admission at SMA Negeri 8 Palembang was well-executed. The steps are planning, organizing, implementing, and monitoring. The response of parents to the implementation that they still have difficulty registering the student’s admission zoning route online and have to prepare requirements documents that must be legalized by the local government. As a result, long before the implementation of student admission, socialization and promotion must be carried out. Admission to the zoning pathway is not an impediment for prospective students who live far from SMA Negeri 8 Palembang.